Terror from the Right:: Revolutionary Terrorism and the Failure of the Weimar Republic - Crim, Brian (Journal of Conflict Studies, 2007)
Abstract The First World War damaged the European psyche, and physically and mentally maimed a whole generation of European men fortunate enough to survive the maelstrom. Nowhere was this more apparent than in post-war and Weimar Germany. For some young German veterans, the war never ended; they simply brought it home to continue the fight in the chaotic streets of the new republic. They revelled in the experience of violence, which they directed against their enemies, real and imagined. Between 1919 and 1923, dozens of loosely organized groups embarked on a campaign of revolutionary terrorism designed to spark a civil war and unite the disparate elements of the German Right behind the goal of creating an authoritarian state. After the failure of the Hitler Putsch in November 1923, the extreme Right altered its tactics and developed sophisticated political organizations capable of competing for influence in the government it once worked to destroy. While the Weimar Republic weathered multiple attempts to bring it down through violence, it was overcome by a combination of internal events and the misguided attempt by the mainstream conservatives to co-opt the Nazis. Assassinations and other terrorist acts alone did not destroy the Weimar Republic, but those responsible for such acts conducted a protracted, multi-faceted effort to undermine its legitimacy. The extreme Right’s early campaign of violence destabilized the Weimar government and both intimidated and enthralled the German people. The Nazis deployed revolutionary terrorism in their political struggle and delivered the death blow to the Weimar Republic.